A Highly pH-Sensitive Fluorescent Membrane Based on Two Dyes Dione and Porphyrine with Close Excitation Peaks - Jiao, C.; Feng, P.Q.; Guo, L.Y.; Dai, H. (Asian Journal of Chemistry, 2015)
A fluorescence pH sensing membrane based on immobilization of two dyes 1-allyloxy-4-hydroxyanthrance-9,10-dione/5-(4-aminophenyl)-10,15,20-triphenylporphyrine with close excitation peaks is prepared and its application for pH sensor are described. Compared to pH 2-4, both dyes showed that presented membrane is highly sensitive to pH variation, with a linear response working range from pH 2 to pH 13.5. The response of sensor is reversible and reproducible.